Conocimientos y actitudes sobre el zika en gestantes del sur de Lima, Perú - Zapatel, Romina (2019)
ABSTRACT OBJECTIVES: To determine knowledge and attitudes about Zika in pregnant women from southern Lima. METHOD: Cross-sectional analytical study. Pregnant women were included who attended the Maternal and Child Health center in Villa María del Triunfo during October 2017. RESULTS: 97 pregnant women participated, the average age was 28.23 ± 7.9. The largest age group was 16-28 years (54.6%). When categorizing the level of knowledge, we appreciate that most had good knowledge about the disease (78.4%) and all had positive attitudes. Pregnant women with a higher educational level had a better knowledge of the disease (p <0.001). CONCLUSIONS: The knowledge and attitudes of the pregnant women about Zika were generally good.